2012
DOI: 10.1007/s00359-012-0740-3
|View full text |Cite
|
Sign up to set email alerts
|

Auditory change detection by a single neuron in an insect

Abstract: The detection of novel signals in the auditory scene is an elementary task of any hearing system. In Neoconocephalus katydids, a primary auditory interneuron (TN-1) with broad spectral sensitivity, responded preferentially to rare deviant pulses (7 pulses/s repetition rate) embedded among common standard pulses (140 pulses/s repetition rate). Eliminating inhibitory input did not affect the detection of the deviant pulses. Detection thresholds for deviant pulses increased significantly with increasing amplitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 35 publications
(51 reference statements)
3
30
1
Order By: Relevance
“…The second mechanism for signal detection under noise is based on novelty detection as described previously (Schul and Sheridan, 2006;Schul et al, 2012;Siegert et al, 2013). The mechanism has two characteristics: broadband interneurons are excited with bursts of APs at the onset of the trill, but show subsequent strong adaptation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The second mechanism for signal detection under noise is based on novelty detection as described previously (Schul and Sheridan, 2006;Schul et al, 2012;Siegert et al, 2013). The mechanism has two characteristics: broadband interneurons are excited with bursts of APs at the onset of the trill, but show subsequent strong adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…However, these interneurons exploit the entire frequency range for responses to unmasked chirps. Schul and Sheridan (2006) described a similar mechanism for the detection of a bat echolocation signal in the presence of a continuous call of a conspecific with reliable responses to the bat call at SNRs of Ϫ18 dB at the masked threshold. Triblehorn and Schul (2013) suggested a model that stimulus-specific adaptation may occur in the dendrites for one signal without preventing a response to the other signal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Neoconocephalus (Orthoptera: Tettigoniidae) TN-1 neuron reliably responded to deviant pulses after responses to common standard pulses ceased, provided the standard and deviant pulses differed sufficiently in their carrier frequency (pitch) (Schul and Sheridan 2006;Schul et al 2012). Extensive physiological testing (Schul et al 2012) revealed that TN-1 adaptation to fast pulse rates did not result from 1) adaptation of its afferents, 2) synaptic depression of the afferent TN-1 excitatory synapses, or 3) known inhibitory inputs to TN-1. However, injection of a calcium chelator into TN-1 significantly delayed the adaptation to repeated stimulation; application of low-sodium saline significantly reduced adaptation to standard pulses (Triblehorn and Schul 2013).…”
mentioning
confidence: 99%